Development of a First Aid Smartphone App for Use by Untrained Healthcare Workers . - Spies, Chel-Marí; Khalaf, Abdelbaset; Hamam, Yskander (My University, 2017)
In the sub-Saharan African context, there is an enormous shortage of healthcare workers, causing communities to experience major deficiencies in basic healthcare. The improvement of basic emergency healthcare can alleviate the lack of assistance to people in emergency situations and improve services to rural communities. The study described in this article, which took place in South Africa, was the first phase of development and testing of an automated clinical decision support system (CDSS) tool for first aid. The aim of the tool, a mobile smartphone app, is that it can assist untrained healthcare workers to deliver basic emergency care to patients who do not have access to, or cannot urgently get to, a medical facility. And the tool seeks to provide assistance that does not require the user to have diagnostic knowledge, i.e., the app guides the diagnostic process as well as the treatment options.
Keywords: first aid, emergency treatment, m-health, smartphone app, clinical decision support system (CDSS), rural healthcare, resuscitation, rule-based algorithms, artificial intelligence (AI), Africa, South Africa